Illustrare un canzoniere: appunti - Battaglia Ricci, Lucia (Cuadernos de Filología Italiana, 2005)
Petrarch didn’t illustrate his Rvf autograph manuscript, but there are some fifteenth century Rvf manuscripts illuminated with an enough complex and varied strategy of illustrating. We felt that it might be of interest to reflect on the Petrarch’s choice of not illuminating his lyric book and to analyse painted illustrations in some Rvf manuscripts to enlighten their visual semantic.
Keywords: Petrach; Canzoniere; illuminated manuscripts